Toxic effects of cadmium chloride on behavior and histopathology of butter catfish Ompok pabda (Hamilton, 1822): Cadmium toxicity on Pabda catfish (Journal of Bangladesh Academy of Sciences, 2024)
Cadmium is very harmful to aquatic organisms and the environment as a toxicant. The present study investigated cadmium's morphological, behavioral, and histopathological effects on Ompokpabda. Initially, the fish were divided into 6 groups and exposed to different concentrations (20 mg/L, 40 mg/L, 80 mg/L, 160 mg/l, 320 mg/L, 400 mg/L) of CdCl2. After 96 hours of exposure, the LC50 value of CdCl2 for O. pabdawas calculated as 190.9 mg/L. Finally, based on LC50, three concentrations of CdCl2 viz., 100 mg/L, 190.9 mg/L, and 300 mg/L, respectively, with three replica and control groups were used to observe morphological, behavioral, and histopathological changes in fish. There were no abnormalities in behavior or deaths in the control group at any point in the experiment. At the same time, the behavioral abnormalities of the CdCl2-treated fish were increased as the dose increased. The behavioral abnormalities observed were loss of balance, breathing difficulty, hyperactivity, frequent surfacing, excessive mucus secretion, and gasping. After 96 hours of exposure to the final treatment, tissue samples (gill and intestine) were collected. Histopathological results revealed clear and significant alterations in the gill and intestine tissues. The alteration in the gill was characterized by hyperplasia of primary and secondary lamellae, epithelial edema, lamellar aneurism, and necrosis. In contrast, the intestine was characterized by intact serosa, less organized mucosa, a consequent fusion of mucosa, and edema between the intestinal submucosa and lamina propria. Compared with the control group, Ompokpabda of treatment groups showed severe intestinal and gill tissue injury. The result revealed that acute cadmium toxicity has a detrimental effect on the exposed fish's normal behavior and essential organs.J. Bangladesh Acad. Sci. 48(2); 217-230: December 2024